HISTORICAL MONUMENTS, SIGHTS AND FAMOUS PEOPLE OF THE COUNTRY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article tells about historical sites and attractions that reflect the rich history and culture of Uzbekistan. Monuments such as the Registan Square of Samarkand, the Shohizinda complex, the Bibi Khanim mosque, the historical center of Bukhara city and the mausoleum of Amir Temur, the Prince demonstrates the tourism potential of the country. The article details the historical significance of these monuments and places, architectural features and their place in the culture of Uzbekistan. The article also highlights the importance of preserving shrines and objects of cultural heritage. The lives of prominent historical figures of Uzbekistan, including allomas such as Amir Temur and Ulughbek, and their role in the history of the country are also covered. The article was written with the aim of helping readers gain a deeper understanding of the historical and cultural resources of Uzbekistan.